Is Davos More Than a Boondoggle? - Sebastian Schmidt; Andrew K. Rose; Andreas Fuchs (ZBW - Leibniz Information Centre for Economics, 2021)
Each year since 1971, the World Economic Forum (WEF) Annual Meeting in Davos, Switzerland, has attracted the leadership of global corporations, governmental and non-governmental organizations, as well as other public figures. However, attending the Davos summit is costly for companies with estimated costs of US 40,000 per delegate. On the one hand, WEF attendance could generate a value added for companies if it generates a business network and buys valuable political support. On the other hand, it could be wasteful in the sense that it generates only private benefits to the attendees themselves without measurable effects for their companies. Our paper is the first to study whether companies draw economic benefits from attending Davos. We introduce a novel database on WEF attendees over the 2009 - 2018 period and match it with firm-level data on stock market performance and corporate ratings. We then use fixed-effects estimations and-in a future version of this paper-a synthetic control method to test whether companies present at Davos perform better. Our donor pool of counterfactual companies consists of MSCI-ACWI corporations from the same sector. Our preliminary findings do not provide evidence that the most famous summit of global leaders creates direct value to businesses.
Keywords: F53; G24; G32; G39; O19; 330; World Economic Forum; international organizations; business leaders; stockmarkets; corporate ratings; summits